Enhanced laser-driven backward proton acceleration using micro-wire array targets - Fan, Lulin; Xu, Tongjun; Wang, Qingsong; Xu, Jiancai; Zhang, Guoqiang; Wang, Putong; Fu, Changbo; Ma, Zhiguo; Deng, Xiangai; Ma, Yugang; Li, Shun; Lu, Xiaoming; et al. (Frontiers in Physics, 2023)
Micro-structured targets can be employed to enhance the coupling of laser energy to the high energy density plasma. Here we report on experimental measurement of enhanced proton beam energy from laser-driven micro-wire array (MWA) targets along the backward direction. An ultra-intense (~2 × 10 20 W/cm 2 ) laser pulse of ~ 40 fs pulse duration interacts with the MWA structure and induces large population of energetic electrons. The enhanced sheath field efficiently accelerates protons both transversely and longitudinally. The spectrometers record proton cut-off energy of around 16 MeV and temperature 813keV along the backward direction, which is 20% − 60% higher than that of a flat target under commensurate laser conditions. Comparison with particle-in-cell simulations suggests that the enhancement originates from the increased temperature and population of the hot electrons within the microwires. These measurements provide a direct probe of the high energy density plasma condition in laser-driven solid targets and a useful benchmark for further studies on laser-driven micro-structured targets.